Unveiling the interplay among skin microbiota, cytokines, and T2DM: an insightful Mendelian randomization study - Zhe Zhang; Chunyu Jiang; Yi-qi Xing; Tianke Yang; Linxuan Zou; Zhuqiang Jia; Lin Zhao; Xin Han; Xueling Qu; Zhen Zhang; Junwei Zong; Shouyu Wang (Nutrition & Metabolism)
Abstract Background Previous observational studies have indicated a correlation between the skin microbiome and Type 2 diabetes (T2DM). It is hypothesized that this causal relationship may be influenced by inflammatory responses. However, these factors as determinants of T2DM remain largely unexplored. Method This study incorporated data from the GWAS database on the skin microbiome, 91 types of inflammatory cytokines, and T2DM. We employed two-sample MR and multivariable MR methods to assess the correlation between the skin microbiome and T2DM, and to investigate whether this correlation is affected by inflammatory cytokines. Results The results of the two-sample MR analysis indicate that within the skin microbiome, genetically predicted genus: Acinetobacter, class: Alphaproteobacteria, genus: Bacteroides, ASV005[Propionibacterium granulosum], and ASV072[Rothia mucilaginosa] are associated with an increased risk of T2DM, while phylum: Proteobacteria, genus: Enhydrobacter, family: Clostridiales, ASV006[Staphylococcus hominis] serve as protective factors against T2DM. Among the inflammatory cytokines, levels of Macrophage colony-stimulating factor 1, Tumor necrosis factor receptor superfamily member 9, Urokinase-type plasminogen activator, and C–C motif chemokine 28 are associated with an increased risk of T2DM. Multivariable MR analysis further revealed that Macrophage colony-stimulating factor 1 levels act as a mediating factor between ASV072[Rothia mucilaginosa] and T2DM. Conclusion In this study, we found a connection between the skin microbiome and T2DM, with inflammatory cytokines playing a key role in this relationship. This research helps us better understand this complex link and shows that addressing inflammation is important for preventing and treating diabetes. This could greatly benefit public health by reducing the impact of diabetes and its complications. Our results suggest that future studies should explore the specific biological interactions between the skin microbiome and diabetes to develop more effective risk management and treatment strategies from a microbial perspective.